Antibacterial nanofiber materials activated by light - Jesenská, Soňa; Plíštil, Lukáš; Kubát, Pavel; Lang, Kamil; Brožová, Libuše; Popelka, Stěpán; Szatmáry, Lórant; Mosinger, Jiří (Journal of biomedical materials research. Part A, 2011)
Electrospun polymeric nanofiber materials doped with 5,10,15,20-tetraphenylporphyrin (TPP) photosensitizer were prepared from four different polymers and were characterized with microscopic methods, steady-state, and time-resolved fluorescence and absorption spectroscopy. The polymers used included polyurethane Larithane™ (PUR), polystyrene (PS), polycaprolactone (PCL), and polyamide 6 (PA6). The antibacterial activity of all nanofiber materials against E. coli was activated by visible light and it was dependent on oxygen permeability/diffusion coefficients and the diameter of the polymeric nanofibers. This activity is based on oxidation ability of singlet oxygen O₂(¹Δ(g)) that is generated upon irradiation. All tested nanofiber materials exhibited prolonged antibacterial properties, even in the dark after long-duration irradiation. The post-irradiation effect was explained by the photogeneration of H₂O₂, which provided the material with long-lasting antibacterial properties.
Keywords: Caprolactam; Anti-Bacterial Agents; Polystyrenes; oxidancia; porfyriny; Light; Porphyrins; Photosensitizing Agents; kaprolaktam; fotosenzibilizující látky; Singlet Oxygen; světlo; peroxid vodíku; polyestery; Polymers; Escherichia coli; Oxidants; nanovlákna; Polyurethanes; antibakteriální látky; Polyesters; polyurethany; Nanofibers; testování materiálů; polymery; singletový kyslík; Hydrogen Peroxide; Materials Testing; polystyreny